RANCANG BANGUN APLIKASI ADMINISTRASI DESA BERBASIS WEBSITE - Hidayanti, Nur; Nuryani, Ely; Fathurohman, Ade Nandang; Kusnadi, Endang (Jurnal Ilmiah Sains dan Teknologi, 2023)
Administration is an administrative activity carried out in the organization using the tools or facilities in the office concerned. Administration is a subsystem in an office organization that serves as the main support of efforts to achieve the organization's overall goals in the form of services into and out of the organization. The purpose of this study is to find out the population administration services carried out by Peucangpari Village to the community. The method carried out in this research is the waterfall method is very suitable in making applications needed in the creation of administrative applications in the current peucangpari village, where the stages of this method are started by analyzing data so that the system will be developed according to user needs. Waterfall method (waterfall model) which begins with research on the current system, design, coding, and maintenance of the system. The results obtained from this study are about village administration applications that can be applied and implemented to assist village parties in providing services to the community.